The degree of the Internet addiction and the psycho-social functioning of young people - Niedorys, Barbara; Kocka, Katarzyna; Ślusarska, Barbara; Chrzan-Rodak, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction: An excess of time devoted to the use of the Internet may cause negative consequences in the mental, physical and social spheres. Psychosocial functioning of youth has a significant role in the regulation of relations with the environment. Deficits in the area of social behavior and interaction with the environment can lead to social isolation and addictions, which addiction to the Internet has an increasing tendency. Aim: To determine the relationship between the psychosocial functioning of young people and the degree of Internet addiction. Material and methods: The surveyed group consisted of 263 respondents. 52.1% were junior high school students, and 47.9% high school. The average age in the group was 15.4 (± 1.4). Almost 25.1% were boys, and 74.9% girls. Among the respondents, 58.9% came from the village, and 41.1% from the city. The data collection was based on the standardized Kimberly Young Test, assessing the degree of Internet addiction and the author’s questionnaire regarding the psychosocial functioning assessment. Results: About 39.3% of students addicted to the Internet admitted that they do not have a large group of friends on whom they can rely. 25% of people addicted to the Internet and 31.6% of the addiction risk group reported difficulties in making new acquaintances. Frequent conflicts with friends were reported by 42.9% of students addicted to the Internet and 31.6% from the risk group. Low self-esteem was felt by as many as 64.3% of addicted students and 42.1% of addiction risk groups. Learning difficulties were reported by as many as 57.1% of the youth addicted to the network. Conclusions: The research results show that in the group of students addicted to the Internet, problems such as difficulties in making new acquaintances, frequent conflicts with peers, lower self-esteem and learning difficulties occurred more often than in people at risk.